Cement-based electrode, method for preparing same, and use thereof
Patent Information
- Application Number
- CN202611283589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]上述两个专利中,在制备水泥基电极时还涉及到切割、打磨抛光等工序,但水泥硬化之后硬度较大,打磨过程中会产生大量粉尘,对于环境和操作人员均不利;同时水泥硬化之后的材料在切割和打磨过程中可能产生表面开裂,且其密度相对较低,难以打磨出如金属般的光滑表面,无法与聚合物基材隔膜内符合,容易刺穿隔膜,导致短路等问题,应用范围受限
基于目前的水泥基超级电容器仍然存在着电学性能不理想或是制备方法复杂、不易操作的问题,例如存在能量密度不高,水泥基电极或水泥基隔膜不抗折,易开裂,循环耐久性能不足等问题,本发明创新地提供了一种改进的电容器,该电容器使用了具备出众性能的电极材料及采用其制备的水泥基电极,进而解决了现有技术存在的上述问题,并且电容器作为一种绿色建筑材料,它能与建筑墙体、楼板等结构直接集成,实现储能设备与建筑构件的一体化安装;
Smart Images

Figure CN123017745A_ABST
Abstract
Description
[0001] This invention is a divisional application of Chinese invention patent application filed on September 17, 2025, with application number 2025113316674 and titled "A cement-based electrode, capacitor and preparation method thereof". Technical Field
[0002] This invention relates to the field of energy storage technology, specifically to a cement-based electrode, its preparation method, and its application. Background Technology
[0003] Since the beginning of the new century, power plants and generating equipment based on clean energy sources such as solar and wind power have been continuously developed and put into use. However, solar and wind power suffer from uneven distribution in time and space, making effective energy storage a key issue for the efficient utilization of clean energy. Chemical energy storage batteries are currently one of the most commonly used energy storage devices in the world, widely applied in automotive, electronics, communications, aerospace, and military fields; however, batteries are generally small in size, have limited capacity, and are relatively expensive, making it difficult to meet the requirements for large-scale and long-term energy storage. Therefore, developing large-capacity, low-cost energy storage devices is crucial to solving the energy storage problem.
[0004] Cement-based supercapacitors have attracted widespread attention from scientists because they can transform an entire building into a giant energy storage device. Cement is one of the most commonly used building materials in the world today. Combining energy storage functions with building materials can enhance the safety of energy storage systems by leveraging the high-temperature resistance and corrosion resistance of building materials. It can also transform building structures into energy storage devices, achieving building energy self-sufficiency, supporting the storage and utilization of renewable energy, and improving building energy efficiency.
[0005] However, current cement-based supercapacitors still suffer from problems such as unsatisfactory electrical performance or complex and difficult-to-operate preparation methods. For example, they have problems such as low energy density, cement-based electrodes or cement-based diaphragms that are not resistant to bending and are prone to cracking, and insufficient cycle durability.
[0006] For example, Chinese invention patent CN 119852100 A discloses an all-cement-based supercapacitor, including a first cement-based electrode, a second cement-based electrode, and a foamed cement insulating layer between the first cement-based electrode and the second cement-based electrode; the first cement-based electrode and the second cement-based electrode are each prepared independently by the following method: a dry mixture is obtained by mixing conductive carbon black and cement, water and water-reducing agent are added and mixed to obtain a cement-based slurry; the cement-based slurry is poured into a mold and vibrated, and after hardening, it is demolded, cured, cut, and polished to obtain the cement-based electrode.
[0007] For example, Chinese invention patent CN 118430985 A discloses a method for preparing a cement-based supercapacitor, including the following steps: Step S1, preparing a nano-carbon black dispersion: Take 5.5% to 7% nano-carbon black material by mass into a container, add 35% to 38.5% water by mass, stir thoroughly and evenly with a magnetic stirrer (A), and then place the container into an ultrasonic cleaner for ultrasonic dispersion to obtain a nano-carbon black dispersion; Step S2, casting: Add 56% to 58% cement by mass to the nano-carbon black dispersion obtained in step S1, stir thoroughly and evenly with a magnetic stirrer (B), then pour into a mold, and compact with a vibrator to obtain a cement matrix through casting; Step S3, curing and drying: After demolding the cement matrix obtained in step S2, place it in a constant temperature curing chamber for curing, and after curing and shaping... The cement substrate is dried, and then the surface of the shaped cement substrate is polished smooth with ultra-fine sandpaper. Step S4: Electrode preparation: The two cement substrates obtained in step S3 are placed into the electrolyte for vacuum saturation. After saturation, they are taken out and the excess electrolyte on the surface of the two cement substrates after vacuum saturation is wiped off with absorbent paper. Then, copper sheets are attached to one side of the surface of the two cement substrates respectively, and connected to the other side of the copper sheets with wires to obtain two electrodes. Step S5: Capacitor preparation: The diaphragm is placed in the electrolyte in step S4 and saturated with vacuum pump. The saturated diaphragm is placed between the two electrodes prepared in step S4 to form a "sandwich" structure. The "sandwich" structure is clamped and fixed with two insulating plates to assemble the cement-based supercapacitor.
[0008] In the two patents mentioned above, the preparation of cement-based electrodes also involves processes such as cutting, grinding and polishing. However, cement has a high hardness after hardening, and a large amount of dust is generated during the grinding process, which is detrimental to the environment and operators. At the same time, the material after cement hardening may crack on the surface during cutting and grinding, and its density is relatively low, making it difficult to grind a smooth surface like metal. It cannot conform to the polymer substrate diaphragm, and is easy to puncture the diaphragm, leading to problems such as short circuits, thus limiting its application range.
[0009] It should be noted that the information disclosed in the background section above is only for understanding the background of this application. Therefore, the background section of this invention may include background information about the problems or environment of this invention, and is not necessarily a description of the prior art. Thus, the content included in the background section does not constitute an admission of the prior art by the applicant. Summary of the Invention
[0010] The purpose of this invention is to overcome one or more shortcomings in the prior art and provide an improved cement-based electrode and capacitor. The capacitor made from the cement-based electrode not only has excellent energy storage performance and mechanical properties, but can also be prepared using a more environmentally friendly and easier-to-operate method.
[0011] The present invention also provides a method for preparing the above-mentioned cement-based electrode and capacitor.
[0012] To achieve the aforementioned building energy storage objectives, the present invention employs the following technical solution: A capacitor includes a first electrode, a separator layer, and a second electrode stacked sequentially, wherein an electrolyte is disposed in the separator layer; The first electrode and the second electrode each independently include a current collector and an electrode material disposed on at least one side of the current collector. The raw materials of the electrode material include cement, coniferous wood fiber, zero-dimensional conductive carbon material, one-dimensional conductive carbon material, sand, and water. The amount of coniferous wood fiber added accounts for 4 wt.%-11 wt.% of the amount of cement added, the amount of zero-dimensional conductive carbon material added accounts for 2 wt.%-13 wt.% of the amount of cement added, the amount of one-dimensional conductive carbon material added accounts for 0.5 wt.%-4 wt.% of the amount of cement added, and the mass ratio of water to cement is 2.5-3.3:1.
[0013] In some embodiments of the present invention, the amount of softwood fiber added accounts for 7 wt.%-10 wt.% of the amount of cement added.
[0014] In some embodiments of the present invention, the amount of the zero-dimensional conductive carbon material added accounts for 4 wt.%-12.5 wt.% of the amount of cement added.
[0015] In some embodiments of the present invention, the amount of the one-dimensional conductive carbon material added accounts for 0.8 wt.%-3.8 wt.% of the amount of cement added.
[0016] In some embodiments of the present invention, the mass ratio of water to cement is 2.5-3.1:1.
[0017] In some embodiments of the present invention, the raw materials of the electrode material, by weight percentage, comprise 18%-30% cement, 1.2%-2.5% coniferous wood fiber, 0.6%-3.5% zero-dimensional conductive carbon material, 0.15%-1.2% one-dimensional conductive carbon material, 6%-12% sand, and 55%-72% water.
[0018] Furthermore, by weight percentage, the raw materials of the electrode material contain 20%-26% cement, 1.6%-2.2% coniferous wood fiber, 1.0%-3.0% zero-dimensional conductive carbon material, 0.3%-0.9% one-dimensional conductive carbon material, 6%-10% sand, and 60%-71% water.
[0019] In some embodiments of the present invention, the raw materials of the electrode material, by weight percentage, comprise 21%-25.5% cement, 1.6%-2.2% coniferous wood fiber, 1.0%-3.0% zero-dimensional conductive carbon material, 0.4%-0.9% one-dimensional conductive carbon material, 6%-10% sand, and 60%-70% water.
[0020] In some embodiments of the present invention, the cement may include, but is not limited to, silicate cement.
[0021] In some embodiments of the present invention, the zero-dimensional conductive carbon material may include, but is not limited to, graphite and / or carbon black.
[0022] In some embodiments of the present invention, the one-dimensional conductive carbon material may include, but is not limited to, carbon fibers and / or carbon nanotubes.
[0023] In some embodiments of the present invention, the sand may include, but is not limited to, quartz sand.
[0024] In some embodiments of the present invention, the membrane layer may include, but is not limited to, glass fiber mesh and / or porous polymer membrane.
[0025] In some embodiments of the present invention, the electrolyte may include, but is not limited to, potassium hydroxide and / or lithium hydroxide.
[0026] In some embodiments of the present invention, the current collector may include, but is not limited to, one or more combinations selected from nickel mesh, aluminum mesh, and carbon paper.
[0027] In some embodiments of the present invention, the length of the coniferous wood fiber is 2-5 mm and the radial dimension is 25-35 μm.
[0028] In some embodiments of the present invention, the particle size of the zero-dimensional conductive carbon material is 10~15μm.
[0029] In some embodiments of the present invention, the length of the one-dimensional conductive carbon material is 6-12 mm and the radial dimension is 5-7 μm.
[0030] In some embodiments of the present invention, the particle size of the sand is less than 5 mm, and more specifically 1 to 3 mm.
[0031] In some embodiments of the present invention, the method for manufacturing the capacitor includes: In the process of preparing the first electrode and the second electrode, the raw materials of the electrode material are mixed and then stacked together with the current collector, and then dehydrated. or, The raw materials for electrode materials are mixed evenly to form an electrode slurry; The electrode slurry and the current collector are layered together and then dehydrated to form the first electrode intermediate. A membrane layer containing an electrolyte is stacked with the first electrode intermediate, and then an electrode slurry and a current collector are sequentially placed on the membrane layer. After dehydration, a capacitor intermediate is obtained, consisting of the first electrode intermediate, the membrane layer containing the electrolyte, and the second electrode intermediate stacked sequentially.
[0032] In some embodiments of the present invention, the dehydration treatment involves removing moisture to below 20%. Further control is maintained at 0.01%-20%, even further at 0.5%-20%, or 1%-20%, or 5%-20%, or 10%-19%, or 12%-18%.
[0033] In some embodiments of the present invention, during the preparation process, electrode slurry after the raw materials of the electrode material are mixed is respectively placed on the opposite side of the current collector.
[0034] Another technical solution provided by the present invention: a method for preparing the capacitor described above, the method comprising: The raw materials for electrode materials are mixed evenly to form an electrode slurry; A layer of electrode slurry is laid flat in the mold, the current collector is laid flat on the electrode slurry, and then another layer of electrode slurry is laid flat on the current collector. After dehydration, the first electrode intermediate is formed. The electrolyte-soaked membrane layer is laid flat on the first electrode intermediate. Then, an electrode slurry, a current collector, and another electrode slurry are sequentially laid flat on the membrane layer. After dehydration, a capacitor intermediate is obtained, consisting of the first electrode intermediate, the membrane layer with electrolyte, and the second electrode intermediate stacked in sequence. The capacitor intermediate is subjected to pressure treatment and curing treatment in sequence.
[0035] In some embodiments of the present invention, the thickness of the electrode paste layer laid flat on either side of the current collector is 1-3 cm.
[0036] In some embodiments of the present invention, the thickness of the current collector is 1-3 mm.
[0037] In some embodiments of the present invention, the thickness of the diaphragm layer is 1-8 mm.
[0038] In some embodiments of the present invention, the pressure of the pressurization process is 15-25 MPa.
[0039] In some embodiments of the present invention, the conditions for the maintenance treatment are: temperature of 20-30°C and relative humidity of 90%-100%.
[0040] Another technical solution provided by the present invention: a cement-based electrode, the cement-based electrode comprising a current collector and an electrode material disposed on at least one side of the current collector, wherein the raw materials of the electrode material include cement, coniferous wood fiber, zero-dimensional conductive carbon material, one-dimensional conductive carbon material, sand and water, wherein the amount of coniferous wood fiber added accounts for 4wt.%-11wt.% of the amount of cement added, the amount of zero-dimensional conductive carbon material added accounts for 2wt.%-13wt.% of the amount of cement added, the amount of one-dimensional conductive carbon material added accounts for 0.5wt.%-4wt.% of the amount of cement added, and the mass ratio of water to cement is 2.5-3.3:1.
[0041] Another technical solution provided by the present invention is: a capacitor as described above, or a capacitor made by the method of preparing the capacitor as described above, or the application of the cement-based electrode as described above in building energy storage structures.
[0042] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: Given that current cement-based supercapacitors still suffer from unsatisfactory electrical performance or complex and difficult-to-operate manufacturing methods, such as low energy density, poor flexural strength of cement-based electrodes or diaphragms leading to cracking, and insufficient cycle durability, this invention innovatively provides an improved capacitor. This capacitor uses electrode materials with outstanding performance and cement-based electrodes prepared using them, thereby solving the aforementioned problems in the prior art. Furthermore, as a green building material, the capacitor can be directly integrated with building walls, floors, and other structures, realizing the integrated installation of energy storage devices and building components. Furthermore, the electrode material in this cement-based electrode (1) is based on a three-dimensional network structure of hydrated silicate with micropores and microcracks formed by cement hardening, which facilitates liquid storage and allows ions to shuttle through it, thus contributing to the construction of ion diffusion channels; (2) the electrode material of this invention uses a water-cement ratio (mass ratio of water to cement) that is significantly higher than that of traditional concrete, which is beneficial to the dispersion of fibers and facilitates the addition of fibers. The addition of fibers will form a certain amount of interfacial gaps in the matrix, which can improve the porosity of the matrix and increase the attachment area of the charge; (3) in particular, this invention selects coniferous wood fiber (or coniferous wood pulp) as a modified One type of fiber material, this fiber is slender and flexible. After being dispersed in the matrix, it can form a continuous multidimensional network structure, which not only enhances the mechanical properties of the electrode to resist the stress impact during charge and discharge cycles, but also optimizes the electrolyte ion transport path through the pore channels between the fibers. At the same time, it provides abundant active sites for the electrode material load. Moreover, the fiber has many branches and tentacles, which can also capture powder and have a certain water-locking effect. In addition, softwood pulp is widely available, inexpensive and easy to degrade, which meets the environmental protection requirements of green energy storage devices. Its natural porous characteristics can also synergistically increase the specific surface area of the electrode, further enhancing the energy storage efficiency and stability of the capacitor. The combined effects of these factors create a rich, gradient-like hierarchical pore distribution in the electrode. Macropores promote ion transport, while mesopores and micropores enhance charge adsorption, thereby optimizing electrolyte wettability and ion diffusion rate, reducing internal resistance, and improving power density and rate performance. At the same time, the high porosity structure provides a larger specific surface area, increasing the contact area between the electrode material and the electrolyte, thus enhancing charge storage capacity and giving the capacitor higher specific capacitance and energy density.
[0043] Furthermore, the improved capacitor of this invention allows for the use of sheet forming processes such as sheet forming, slurry forming, or molding. Compared to the compaction process of ordinary concrete, the removal of internal gas is more difficult, resulting in the presence of micropores and increased overall porosity. The higher water-cement ratio in the electrode material allows the electrode slurry to flow freely, enabling it to be layered with current collectors and diaphragms in a mold. Combined with a dehydration process, the electrode slurry undergoes preliminary drying and shaping after dehydration, ensuring full adhesion to the current collector and diaphragm layers. Moreover, since the cement is not yet fully dissolved at this stage... The electrode slurry exhibits initial hydration and setting, thus preventing puncture of the diaphragm when bonded to the diaphragm layer material. Furthermore, because the electrode slurry has undergone dehydration treatment, it is unlikely to wet or penetrate the diaphragm layer. This prevents the diaphragm from being punctured after hardening during later hydration processes, avoiding short circuits between the electrodes on both sides of the diaphragm layer. In contrast, existing technologies require the fabrication of cement-based electrodes, which necessitate cutting and grinding to obtain a smooth surface before assembly with the diaphragm. This process is complex, and the cutting and grinding processes can damage the cement-based materials and generate dust. Attached Figure Description
[0044] Figure 1 This is a schematic diagram of the capacitor manufacturing process in an embodiment of the present invention; Figure 2 This is a 10x magnified image of coniferous wood fibers under a microscope. Figure 3 This is a microscope image of polyacrylic acid fiber magnified 4x. Figure 4 The CV curves are from Examples 1-4 of this invention; Figure 5 The GCD curves are those of Examples 1-4 of this invention; Figure 6 The CV curves are those of Comparative Examples 1-5 of this invention; Figure 7 Scanning electron microscope image of the sample with single carbon fiber doping in Comparative Example 2; Figure 8 Scanning electron microscope image of the graphite-doped sample in Comparative Example 3. Detailed Implementation
[0045] The purpose of this invention is to design an energy-storing capacitor (hereinafter also referred to as a fiber cement flat-plate supercapacitor) that combines traditional building materials with energy storage technology to overcome the limitations of existing supercapacitors in terms of mechanical strength, environmental adaptability, and building integration. This fiber cement flat-plate supercapacitor can be used as an exterior wall, interior wall, or ceiling in buildings. This design not only achieves the integration of energy storage devices with the building structure but also provides an innovative solution for distributed energy storage in green buildings. It boasts advantages such as low cost, easy mass production, and environmental friendliness, promoting the development of building-energy synergy systems.
[0046] This invention provides a cement-based supercapacitor as a distributed energy storage solution in green buildings, comprising fiber cement flat plate electrodes, a membrane material, and an electrolyte material.
[0047] As a preferred option: softwood pulp is selected as one of the fibers in the fiber cement board. Conductive phase materials such as carbon fiber, graphite, carbon nanotubes, and carbon black are added to the fiber cement board. Nickel mesh, aluminum mesh, and carbon paper are embedded in the fiber cement board as current collectors. Glass fiber mesh and porous polymer membranes are used as membrane materials, and KOH and LiOH are used as electrolyte materials.
[0048] Furthermore, the present invention specifically provides a capacitor comprising a first electrode, a separator layer, and a second electrode stacked sequentially, wherein an electrolyte is disposed in the separator layer; the first electrode and the second electrode each independently include a current collector and an electrode material disposed on at least one side of the current collector, wherein the raw materials of the electrode material include cement, coniferous wood fiber, zero-dimensional conductive carbon material, one-dimensional conductive carbon material, sand, and water.
[0049] Preferably, the amount of coniferous wood fiber added accounts for 4wt.%-11wt.% of the amount of cement added, the amount of zero-dimensional conductive carbon material added accounts for 2wt.%-13wt.% of the amount of cement added, the amount of one-dimensional conductive carbon material added accounts for 0.5wt.%-4wt.% of the amount of cement added, and the mass ratio of water to cement is 2.5-3.3:1.
[0050] In the electrode material of this invention, cement is a gel material with silicate as its main component, which, after hardening, forms a porous three-dimensional network structure of hydrated calcium silicate. Due to the presence of micropores and microcracks, cement concrete can store liquid and allow ions to shuttle within it. When no current flows, positively and negatively charged ions are randomly distributed within the solution; when an electric field is present, the positively and negatively charged ions are arranged in an ordered manner. There are many examples of ion migration through hardened cement-based materials. For instance, chloride ions are considered a major cause of corrosion of embedded steel bars in concrete; chloride ions can enter the concrete interior through an interconnected pore network via absorption, diffusion, and capillary action. The corrosion process of steel bars in concrete is another example of ion flow through hardened cement materials. The transport of ions in cement-based materials makes them suitable as the main material for capacitors.
[0051] In the electrode material of this invention, the dispersion of the fibers themselves forms a certain amount of interfacial gaps in the matrix. Simultaneously, a high water-cement ratio not only adapts to the dispersion of the fibers, but the presence of the fibers also hinders the filling efficiency of cement hydration products by reducing their obstruction of cement particles. Furthermore, the interfacial transition zone between the fibers and the cement matrix is prone to insufficient bonding, forming micropores. This results in a greater variety of micropores or mesopores of different sizes, further improving the pore structure and increasing the charge adhesion area. In addition, the addition of carbon fibers not only improves conductivity, but the rigid framework they provide effectively inhibits shrinkage and cracking of the cement paste. Combined with flexible fibers such as coniferous wood fibers, the bridging effect reduces stress concentration. The resulting matrix cracking is beneficial to improving the flexural strength of the electrode. Moreover, after dispersion in the matrix, it can construct a continuous multidimensional network structure, which not only enhances the mechanical properties of the electrode to resist stress impact during charge and discharge cycles, but also optimizes the electrolyte ion transport path through the pore channels between fibers. At the same time, it provides abundant active sites for electrode material loading. Furthermore, the numerous branches and tendrils of coniferous wood fibers can also capture / adsorb powder and have a certain water-locking effect, providing more crystal nucleation sites. In addition, coniferous wood pulp is widely available, inexpensive, and easily degradable, which meets the environmental protection requirements of green energy storage devices. Its natural porous characteristics can also synergistically increase the specific surface area of the electrode, further enhancing the energy storage efficiency and stability of the capacitor. Furthermore, the high porosity and excellent mechanical properties of the constructed electrode make it a good carrier for cement-based supercapacitors. Its porous structure provides abundant electrode reaction interfaces, and the high and uniform porosity facilitates the rapid migration and adsorption of electrolyte ions, significantly improving capacitance performance. The incorporation of different types of fibers enhances the mechanical strength and flexibility of the electrode, solving the problem of easy cracking of traditional electrode materials and extending the service life of the device. As an inorganic non-metallic material, it has good chemical stability and high temperature resistance, and can adapt to complex working environments.
[0052] High-performance capacitors consist of electrodes with good electrical conductivity and an electrolyte with high ionic conductivity. This invention uses one-dimensional conductive carbon materials, such as carbon fiber, and zero-dimensional conductive carbon materials, such as graphite, as the conductive phase materials. Their combined use significantly improves the conductivity of the electrode slurry. The combined use of these two materials also facilitates the formation of interconnected network-like conductive channels, providing a prerequisite for the conduction of free charge carriers. The membrane material of this invention uses glass fiber mesh or porous polymer materials, which have high compatibility with cement-based materials and can adapt to alkaline conditions in cement-based environments. This invention uses alkaline substances such as potassium hydroxide and lithium hydroxide as electrolytes, and uses an alkaline solution formed by their aqueous solutions as the electrolyte.
[0053] The capacitor of this invention employs electrodes with a rich porous structure, and the high porosity of the electrodes significantly improves the capacitor's performance. Firstly, the high porosity structure provides a larger specific surface area, increasing the contact area between the electrode material and the electrolyte, thereby enhancing charge storage capacity and giving the capacitor higher specific capacitance and energy density. Secondly, the rich porous structure (especially the hierarchical pore distribution: macropores promote ion transport, while mesopores and micropores enhance charge adsorption) optimizes electrolyte wettability and ion diffusion rate, reduces internal resistance, and improves power density and rate performance. Furthermore, the improved capacitor of this invention allows for the use of sheet forming, slurry forming, or molding processes. The high water-cement ratio in the electrode material allows the electrode slurry to flow freely, enabling it to be layered with current collectors and diaphragms in a mold. Combined with a dehydration process, the electrode slurry achieves initial drying and shaping after dehydration, ensuring thorough adhesion to the current collector and diaphragm layers. Since the cement has not yet undergone significant hydration and initial setting, it will not puncture the diaphragm when adhering to the diaphragm layer. Simultaneously, because the electrode slurry has undergone dehydration, it is unlikely to wet or penetrate the diaphragm layer, thus preventing puncture of the diaphragm after hardening during later hydration and avoiding short circuits between the electrodes on both sides of the diaphragm layer. In contrast, existing technologies require the fabrication of cement-based electrodes, which must be cut and polished to obtain a smooth surface before assembly with the diaphragm. This process is complex, and the cutting and polishing can damage the cement-based materials and generate dust.
[0054] The capacitor of this invention, as a green building material, can be directly integrated with building walls, floors and other structures to achieve integrated installation of energy storage devices and building components; at the same time, the material is widely available and inexpensive, providing a new approach for the development of new green energy storage devices.
[0055] In this invention, the length of the coniferous wood fibers is 2-5 mm, and the radial dimension is 25-35 μm. The coniferous wood fibers can be added in the form of coniferous wood fiber pulp, which is a fiber raw material made from coniferous wood through a pulping process. For example, it can be prepared by adding paperboard of the corresponding coniferous tree (e.g., paperboard purchased from Arauco in Chile) to water and beating it until a pulp containing coniferous wood fibers of the corresponding size is produced. This pulp can be prepared by conventional methods in the art or obtained commercially. Coniferous wood fibers have a special microstructure, the microstructure diagram of which can be found in [reference needed]. Figure 2 As shown, in the system of this invention, coniferous wood fiber, compared to other fiber materials such as polyacrylic acid fiber (microstructure diagram as shown), Figure 3 (As shown) It has better effects, and the improvement in mechanical performance and energy storage performance is more significant.
[0056] Zero-dimensional conductive carbon materials include, but are not limited to, graphite and / or carbon black, with a particle size of 10-15 μm, and are commercially available or prepared according to conventional methods in the art.
[0057] One-dimensional conductive carbon materials include, but are not limited to, carbon fibers and / or carbon nanotubes with a length of 6-12 mm and a radial dimension of 5-7 μm, which are commercially available or prepared according to conventional methods in the art.
[0058] The method for preparing the capacitor of the present invention includes: mixing the raw materials of the electrode material to form an electrode slurry; spreading a layer of electrode slurry in a mold, spreading a current collector on the electrode slurry, spreading another layer of electrode slurry on the current collector, and performing dehydration treatment to form a first electrode intermediate; spreading a membrane layer wetted with electrolyte on the first electrode intermediate, and then spreading a layer of electrode slurry, a current collector, and another layer of electrode slurry sequentially on the membrane layer, and performing dehydration treatment to obtain a capacitor intermediate composed of a first electrode intermediate, a membrane layer containing electrolyte, and a second electrode intermediate arranged in sequence; and performing pressure treatment and curing treatment on the capacitor intermediate sequentially.
[0059] The following is combined Figure 1 The manufacturing process of the capacitor of the present invention will be further explained as follows: Step 1: Mix the raw materials in the electrode material. For example, the raw materials can be poured into a mixer according to the formula for batching. Step 2: Mix all raw materials thoroughly using a mixer to prepare electrode slurry for later use. Step 3: Take the electrode slurry and place it into a molding die. For example, first lay a layer of electrode slurry (also called blank) in the die. The thickness of the electrode slurry can be very thin or relatively thick, for example, it can be set to 1-3cm. The die is equipped with a drawer plate (with large pores to facilitate subsequent dehydration). At the same time, a layer of felt is placed on the drawer plate. The felt acts as a filter paper to facilitate subsequent dehydration and prevent the leakage of particles in the electrode slurry. In addition, a water inlet and a cleaning port are opened on the side of the die base. The water inlet is used for subsequent water pumping, and the cleaning port is used for cleaning the die after preparation. Step 4: Based on step 3, spread the current collector evenly on the electrode slurry (also known as the blank); Step 5: Based on step 4, continue to add electrode slurry to the current collector, that is, continue to spread a layer of electrode slurry (also called blank). The thickness of the electrode slurry can be very thin or relatively thick, for example, it can be set to 1-3cm. Then, dewatering treatment is carried out. The dewatering treatment can be done by connecting a pump to a water inlet and then extracting the excess water from the slurry until the water content is reduced to below 20%. If necessary, a trowel can be used to smooth the surface of the slurry. Step 6: Based on step 5, spread the electrolyte-soaked membrane material (membrane layer) evenly onto the dehydrated electrode slurry (also known as the blank); wherein, the electrolyte-soaked membrane material (membrane layer) can be obtained by immersing the membrane material (membrane layer) in the electrolyte until saturation; Step 7: Based on step 6, continue to add electrode paste on the diaphragm layer, that is, continue to lay a layer of electrode paste (also called blank). The thickness of the electrode paste can be very thin or relatively thick, for example, it can be set to 1-3cm. Step 8: Based on step 7, spread the current collector evenly on the electrode slurry (also known as the blank); Step 9: Based on step 8, continue to add electrode slurry to the current collector, that is, continue to spread a layer of electrode slurry (also called blank). The thickness of the electrode slurry can be very thin or relatively thick, for example, it can be set to 1-3cm. Then, dewatering treatment is carried out. The dewatering treatment can be carried out by connecting a pump to a water inlet and then extracting the excess water from the slurry until the water content is reduced to below 20%. If necessary, a trowel can be used to smooth the surface of the slurry. Then, the obtained wet blank, i.e. the capacitor intermediate, is taken out and placed in a press. The pressure is slowly applied to 15-25MPa and held for 5-60 minutes. Then it is placed in a standard curing chamber for curing. After step 10 and curing are completed, the capacitor of the present invention (also known as fiber cement flat plate supercapacitor) is obtained.
[0060] The above-mentioned solution will be further described below with reference to specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0061] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0062] Silicate cement, purchased from Anhui Conch Cement Co., Ltd., grade 52.5; softwood fiber, approximately 3m in length and approximately 30μm in radial dimension (Note: In the following examples, the softwood fiber is added in the form of softwood fiber pulp (the mass concentration of softwood fiber in the pulp is 4%, and the size is the corresponding size mentioned above). For the sake of illustrating the specific content, it is converted to the corresponding content of softwood fiber and water); graphite, particle size approximately 10~15μm; carbon fiber, approximately 6mm in length and 5~7μm in radial dimension; quartz sand, particle size approximately 2mm; polyacrylic acid fiber, approximately 3mm in length and 28μm in radial dimension, purchased from Yong'an Baohualin Industrial Development Co., Ltd.; glass fiber mesh, approximately 2mm thick and 1.63μm in pore size; nickel foam, approximately 2mm thick and 0.5mm in pore size.
[0063] Example 1: This example provides a capacitor and its manufacturing method. The capacitor includes a first electrode, a separator layer, and a second electrode stacked sequentially, and an electrolyte is disposed in the separator layer. use Figure 1 The capacitor in this example is prepared using the above-described preparation process, specifically including the following steps: Step ①: Pour all raw materials into a mixer according to the electrode material formula for batching; by weight percentage, the electrode slurry contains: 22% silicate cement, 2% softwood fiber, 68% water, 0.2% carbon fiber, 1.3% graphite, and 6.5% quartz sand; Step 2: Mix all raw materials thoroughly using a mixer to prepare electrode slurry for later use. Step 3: Take the electrode paste and put it into the molding die. Specifically, first spread a layer of electrode paste (also called blank) in the die. The thickness of the electrode paste is 1cm. Step 4: Based on step 3, spread the current collector evenly on the electrode slurry (also known as the blank); Step 5: Based on step 4, continue to add electrode slurry to the current collector, that is, continue to spread a layer of electrode slurry (also called blank). The thickness of the electrode slurry is 1cm. Then, dehydrate it until the moisture is removed to 18%. Use a trowel to smooth the surface of the slurry. Step 6: Based on step 5, the membrane material (membrane layer) soaked in electrolyte is spread evenly on the dehydrated electrode slurry (also known as the blank); wherein, the membrane material (membrane layer) soaked in electrolyte is obtained by immersing the membrane material (membrane layer) in electrolyte until saturation; Step 7: Based on step 6, continue to add electrode paste on the diaphragm layer, that is, continue to lay a layer of electrode paste (also called blank), the thickness of the electrode paste is 1cm; Step 8: Based on step 7, spread the current collector evenly on the electrode slurry (also known as the blank); Step 9: Based on step 8, continue to add electrode slurry to the current collector, that is, continue to spread a layer of electrode slurry (also called blank). The thickness of the electrode slurry is 1cm. Then, dehydrate it until the moisture is removed to 18%. Use a trowel to smooth the surface of the slurry. The obtained wet blank, i.e. the capacitor intermediate, is taken out and placed in a press. The pressure is slowly applied to 20MPa and held for 20 minutes. Then it is placed in a standard curing chamber for curing. The curing conditions are: temperature 25±2℃ and humidity 100%RH. After step 10 and curing are completed, a capacitor (also known as a fiber cement flat-plate supercapacitor) is obtained.
[0064] The membrane layer is made of glass fiber mesh, the electrolyte is potassium hydroxide, the electrolyte solution is a 6 mol / L potassium hydroxide aqueous solution, and the current collector is nickel foam.
[0065] Example 2: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 23% silicate cement, 2% coniferous wood fiber, 65% water, 0.5% carbon fiber, 1% graphite, and 8.5% quartz sand.
[0066] Example 3: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 23% silicate cement, 2% coniferous wood fiber, 64% water, 0.5% carbon fiber, 2.5% graphite, and 8% quartz sand.
[0067] Example 4: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 24% silicate cement, 1.7% coniferous wood fiber, 60.8% water, 0.9% carbon fiber, 2.9% graphite, and 9.7% quartz sand.
[0068] Comparative Example 1: This example provides a capacitor and its preparation method, which is basically the same as in Example 1, except that the coniferous wood fiber is replaced with an equal weight of polyacrylic acid fiber.
[0069] Comparative Example 2: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 22% silicate cement, 2% coniferous wood fiber, 68% water, 1.5% carbon fiber, and 6.5% quartz sand.
[0070] Comparative Example 3: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 22% silicate cement, 70% water, 1.5% graphite, and 6.5% quartz sand.
[0071] Comparative Example 4: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 28.7% silicate cement, 2% coniferous wood fiber, 55.5% water, 1% carbon fiber, 3.4% graphite, and 9.4% quartz sand; and no dehydration treatment is performed in the preparation method. Specific preparation methods include: Step 1: Pour all raw materials into a mixer according to the electrode material formula for batching; Step 2: Mix all raw materials thoroughly using a mixer to prepare electrode slurry for later use. Step 3: Take the electrode paste and put it into the molding die. Specifically, first spread a layer of electrode paste (also called blank) in the die. The thickness of the electrode paste is 1cm. Step 4: Based on step 3, spread the current collector evenly on the electrode slurry (also known as the blank); Step 5: Based on step 4, continue to add electrode slurry to the current collector, that is, continue to spread a layer of electrode slurry (also called blank). The thickness of the electrode slurry is 1cm. Use a trowel to smooth the surface of the slurry, and then let it stand for 1 hour to allow the wet blank to have a certain initial setting strength. Step 6: Based on step 5, the membrane material (membrane layer) soaked in electrolyte is spread evenly on the initially solidified electrode slurry (also known as the blank); wherein, the membrane material (membrane layer) soaked in electrolyte is obtained by immersing the membrane material (membrane layer) in electrolyte until saturation; Step 7: Based on step 6, continue to add electrode paste on the diaphragm layer, that is, continue to lay a layer of electrode paste (also called blank), the thickness of the electrode paste is 1cm; Step 8: Based on step 7, spread the current collector evenly on the electrode slurry (also known as the blank); Step 9: Based on step 8, continue to add electrode slurry to the current collector, that is, continue to spread a layer of electrode slurry (also called blank). The thickness of the electrode slurry is 1cm. Use a trowel to smooth the surface of the slurry. When the wet blank reaches the final setting strength, the capacitor intermediate is taken out and placed in the press. The pressure is slowly applied to 20MPa and held for 20 minutes. Then it is placed in the standard curing chamber for curing. The curing conditions are: temperature 25±2℃ and humidity 100%RH. After step 10 and curing are completed, the capacitor is obtained.
[0072] Comparative Example 5: This example provides a capacitor and its preparation method, which are basically the same as in Example 1, except that: by weight percentage, the electrode slurry contains: 25.9% silicate cement, 0.7% coniferous wood fiber, 62.2% water, 1% carbon fiber, 9.9% quartz sand, and 0.3% graphite.
[0073] Performance testing: (1) The capacitors obtained in Examples 1-4 and Comparative Examples 1-5 were subjected to the following performance tests. The specific results are shown in Table 1.
[0074] The test method for flexural strength (MPa) is GB / T 7019-2024.
[0075] The method for testing electrode resistivity (Ω·cm) is the four-electrode method.
[0076] The specific capacitance (F / g) test method is: Blue Battery Test System (10mA constant current charge and discharge).
[0077] The energy density (Wh / L) test method is: Blue Battery Test System (10mA constant current charge and discharge).
[0078] Table 1 In Comparative Example 1, replacing coniferous wood fiber with an equal weight of polyacrylic acid fiber resulted in a significant decline in various performance aspects. Analysis suggests this is related to the unique microstructure of coniferous wood fiber, which has a high fibrillation rate, numerous branches and tendrils, and a rough surface that facilitates the anchoring of active materials. These branches can also attach more cement particles, reducing powder loss during vacuuming and creating better pore structures, thus improving ion transport efficiency and overall electrode strength and energy storage performance. In contrast, Comparative Example 1, replacing coniferous wood fiber with polyacrylic acid fiber, not only resulted in lower strength but also insufficient energy storage performance. This may be due to its smoother surface, fewer cement particle attachment sites, and the risk of cement-based particle slippage. Its microstructure is significantly different from coniferous wood fiber, resulting in insufficient improvement in capacitor performance and potentially even negative impacts. In Comparative Example 2, adding only a large amount of carbon fiber without adding graphite resulted in a decrease in both strength and energy density. Furthermore, while resistivity decreased, this was likely due to the excessive amount of carbon fiber. However, on the one hand, carbon fiber is more than 10 times more expensive than graphite, and increasing the carbon fiber content would significantly increase the cost of the capacitor, hindering large-scale production. On the other hand, the resistivity did not decrease significantly, likely due to the poor continuity of the conductive network formed by the carbon fiber in the cement-based material (see...). Figure 7 Some fibers are dispersed in parallel within the matrix and are not directly connected, meaning that not all the carbon fibers are actually utilized.
[0079] In Comparative Example 3, only graphite was added, without any softwood fiber or carbon fiber. Firstly, powder loss was significant. Softwood fiber contains numerous tendrils that effectively adsorb powdered materials such as cement and graphite. Without softwood fiber, powder loss occurs during water extraction, affecting the electrical and mechanical properties of the board. Secondly, the addition of graphite alone leads to a discontinuous conductive network within the matrix. Although graphite particles are uniformly dispersed within the cement-based material, the large gaps between particles and their lack of cohesion easily affect the matrix's conductivity (see scanning electron microscope image). Figure 8 (as shown) In Comparative Example 4, no dehydration process was performed, so the water-cement ratio was added at a relatively low proportion. At the same time, the amount of conductive material graphite added was also increased accordingly, resulting in a decrease in flexural strength. In addition, this preparation process without dehydration treatment requires the cement-based material to hydrate itself to generate strength, so the cement needs to be allowed to set between layers, which takes a long time. Furthermore, since this structure is a layered structure, when the slurry is poured after initial setting, the electrode material may penetrate the diaphragm material, causing the positive and negative electrodes to overlap, which poses a short circuit risk and seriously affects the energy density of the fiber cement flat-plate supercapacitor.
[0080] In Comparative Example 5, the imbalance in the proportions of the raw materials not only significantly reduced the strength but also increased the resistivity. Analysis suggests that the excessive carbon fiber content in this example may easily lead to carbon fiber agglomeration, affecting the electrode strength. Simultaneously, the insufficient coniferous fiber content may also affect the pore structure of the electrode material, thus easily reducing the energy density of the fiber cement flat-plate supercapacitor and potentially causing graphite loss during water pumping. Conversely, the reduced graphite content may affect the effective bonding of linear and powdered conductive phase materials, hindering the formation of a stable three-dimensional conductive pathway within the electrode. Therefore, compared to the example, the capacitor in Comparative Example 5 has a higher resistivity. Furthermore, carbon fiber is more than 10 times more expensive than graphite; increasing the carbon fiber content will also increase the cost of the capacitor, hindering large-scale production.
[0081] (2) In order to test the electrochemical performance of different embodiments and comparative examples, the inventors used a battery testing system to measure the CV curves (cycle-voltammetry curves) of different embodiments and comparative examples, and used a battery performance testing system to test the GCD curves of different embodiments and comparative examples. Figure 4 The CV curves for Examples 1-4 are derived from... Figure 4 As can be seen, the CV curve tends to be rectangular at lower scan rates, indicating its typical double-layer characteristics. Even at a scan rate of 500 mV / s, it maintains a rectangular shape, confirming the formation of an efficient double layer within the electrode structure and rapid ion dynamics in the device. Furthermore, with the improvement of the electrode material's conductivity, the CV curve tends to be even more rectangular at the same scan rate. Figure 5 The GCD curves for Examples 1-4 under 3mA constant current charge-discharge are shown below. Figure 5 It can be seen that in the implementation cases, the GCD curves are close to isosceles triangles under a current of 3mA, indicating the ultrafast charging / discharging performance of the electrode.
[0082] Figure 6 The CV curves are shown in Comparative Examples 1-5. The area under the CV curve can qualitatively characterize the capacitance of a capacitor. Figure 6 It can be seen that the closed areas of the CV curves of Comparative Example 1 and Comparative Example 3 are relatively small. This is because in Comparative Example 1, replacing all the coniferous wood fibers with PVA fibers leads to the loss of cement, graphite, and other powder materials in the matrix during the vacuuming process. The loss of these powder materials reduces the strength and conductivity of the matrix. Comparative Example 3 did not add coniferous wood fibers or carbon fibers. The absence of coniferous wood fibers leads to the loss of cement, graphite, and other powder materials, affecting the mechanical and electrical properties of the capacitor (same as Comparative Example 1). The system contains only graphite, which results in discontinuity of the conductive phase material in the matrix (see...). Figure 8 As shown), this further affects the conductivity of the board, ultimately resulting in the worst energy density and other properties. The system in Comparative Example 2, containing only carbon fibers, also makes it difficult to form complete conductive pathways within the matrix (see...). Figure 7 As shown in the figure, this results in poor conductivity of the electrode material, thus affecting the energy density and other properties of the plate. The CV curve closure area of Comparative Example 4 is the largest compared to the other comparative examples, mainly because Comparative Example 4 has a more complete material set, ensuring the mechanical and electrical properties of the plate. However, because Comparative Example 4 did not use a vacuum, the plate forming process required waiting for the wet blank to reach a certain strength before pressurization, thus prolonging the forming time. Furthermore, due to its layered structure, when pouring the slurry after initial setting, the electrode material may penetrate the diaphragm material, causing the positive and negative electrodes to overlap, posing a short-circuit risk. Comparative Example 5 has a lower content of coniferous wood fiber, leading to the loss of cement, graphite, and other powders, thus affecting the conductivity of the plate and ultimately impacting the energy density of the fiber cement parallel plate capacitor. Figure 6 It can also be seen that the area of closure of the CV curve in Comparative Example 5 is smaller than that in Comparative Examples 2 and 4.
[0083] In summary, the capacitor of this invention not only has excellent energy storage performance and mechanical properties, realizing the integration of energy storage devices and building structures, but also has advantages such as low cost, easy mass production, and environmentally friendly manufacturing process, thus promoting the development of building-energy synergy systems.
[0084] As used throughout the specification and claims, the term "comprising" is an open-ended term and should be interpreted as "comprising but not limited to." "Substantially" means that within an acceptable margin of error, those skilled in the art can solve the technical problem and substantially achieve the technical effect. It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a product or system comprising a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a product or system. Without further limitations, an element defined by the phrase "comprising one" does not exclude the presence of other identical elements in the product or system comprising said element.
[0085] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
[0086] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
Claims
1. A cement-based electrode, characterized in that, The cement-based electrode includes a current collector and an electrode material disposed on at least one side of the current collector. The raw materials of the electrode material include cement, coniferous wood fiber, zero-dimensional conductive carbon material, one-dimensional conductive carbon material, sand, and water. The amount of coniferous wood fiber added accounts for 4 wt.%-11 wt.% of the total cement content, the amount of zero-dimensional conductive carbon material added accounts for 2 wt.%-13 wt.% of the total cement content, and the amount of one-dimensional conductive carbon material added accounts for 0.5 wt.%-4 wt.% of the total cement content. The mass ratio of water to cement is 2.5-3.3:
1. By weight percentage, the cement accounts for 18%-30% of the raw materials of the electrode material.
2. The cement-based electrode according to claim 1, characterized in that, By weight percentage, the cement accounts for 20%-26% of the raw materials of the electrode material; and / or, the mass ratio of water to cement is 2.5-3.1:
1.
3. The cement-based electrode according to claim 1, characterized in that, By weight percentage, the cement accounts for 21%-25.5% of the raw materials of the electrode material; and / or, the amount of softwood fiber added accounts for 7wt.%-10wt.% of the amount of cement added.
4. The cement-based electrode according to claim 1, characterized in that, By weight percentage, the coniferous wood fiber accounts for 1.2%-2.5% of the raw materials of the electrode material; and / or, the length of the coniferous wood fiber is 2-5 mm and the radial dimension is 25-35 μm.
5. The cement-based electrode according to claim 1, characterized in that, By weight percentage, the raw materials of the electrode material contain 1.6%-2.2% coniferous wood fiber; and / or, the amount of zero-dimensional conductive carbon material added accounts for 4wt.%-12.5wt.% of the amount of cement added; and / or, the amount of one-dimensional conductive carbon material added accounts for 0.8wt.%-3.8wt.% of the amount of cement added.
6. The cement-based electrode according to claim 1, characterized in that, By weight percentage, the raw materials of the electrode material contain 0.6%-3.5% zero-dimensional conductive carbon material, 0.15%-1.2% one-dimensional conductive carbon material, 6%-12% sand, and 55%-72% water; and / or, the cement is silicate cement; and / or, the zero-dimensional conductive carbon material is graphite and / or carbon black; and / or, the one-dimensional conductive carbon material is carbon fiber and / or carbon nanotubes; and / or, the sand is quartz sand.
7. The cement-based electrode according to claim 1, characterized in that, The zero-dimensional conductive carbon material has a particle size of 10-15 μm; and / or, the one-dimensional conductive carbon material has a length of 6-12 mm and a radial dimension of 7-10 μm; and / or, the sand has a particle size of less than 5 mm; and / or, by weight percentage, the raw materials of the electrode material contain 20%-26% cement, 1.6%-2.2% coniferous wood fiber, 1.0%-3.0% zero-dimensional conductive carbon material, 0.3%-0.9% one-dimensional conductive carbon material, 6%-10% sand, and 60%-71% water.
8. The cement-based electrode according to claim 1, characterized in that, The current collector is selected from one or more combinations of nickel mesh, aluminum mesh, and carbon paper; and / or, the thickness of the current collector is 1-3 mm; and / or, the thickness of the electrode material disposed on at least one side of the current collector is 1-3 cm; and / or, the particle size of the sand is 1-3 mm; and / or, by weight percentage, the raw materials of the electrode material contain 21%-25.5% cement, 1.6%-2.2% coniferous wood fiber, 1.0%-3.0% zero-dimensional conductive carbon material, 0.4%-0.9% one-dimensional conductive carbon material, 6%-10% sand, and 60%-70% water.
9. A method for preparing a cement-based electrode according to any one of claims 1-8, characterized in that, The preparation method includes: The raw materials for electrode materials are mixed evenly to form an electrode slurry; The electrode slurry and current collector are layered together and then dehydrated.
10. The method for preparing a cement-based electrode according to claim 9, characterized in that, The dehydration process involves removing moisture to below 20%, further controlling it to 0.01%-20%, even further controlling it to 0.5%-20%, or 1%-20%, or 5%-20%, or 10%-19%, or 12%-18%.
11. The method for preparing a cement-based electrode according to claim 9, characterized in that, The method for preparing the cement-based electrode includes: The electrode slurry is prepared by mixing the various raw materials of the electrode material through the stirring action of the mixer. A layer of electrode slurry is laid flat in the mold, the current collector is laid flat on the electrode slurry, and then another layer of electrode slurry is laid flat on the current collector for dehydration treatment.
12. The method for preparing a cement-based electrode according to claim 11, characterized in that, The mold is equipped with a drawer plate for dehydration and a cloth on the drawer plate for filtering. The first layer of electrode paste is laid flat in the mold on the cloth.
13. The application of a cement-based electrode according to any one of claims 1-8, or a cement-based electrode prepared by any one of claims 9-12, in the preparation of a capacitor, wherein the capacitor comprises a first electrode, a diaphragm layer, and a second electrode arranged in sequence, wherein an electrolyte is disposed in the diaphragm layer, and both the first electrode and the second electrode are the cement-based electrodes.
14. A capacitor, characterized in that, The capacitor is prepared by the following method: The raw materials for electrode materials are mixed evenly to form an electrode slurry; The electrode slurry and the current collector are layered together and then dehydrated to form the first electrode intermediate. A membrane layer containing an electrolyte is stacked with the first electrode intermediate, and then an electrode slurry and a current collector are sequentially placed on the membrane layer. After dehydration, a capacitor intermediate is obtained, consisting of the first electrode intermediate, the membrane layer containing an electrolyte, and the second electrode intermediate stacked sequentially. The capacitor intermediate is subjected to sequential pressure treatment and curing treatment; The electrode material comprises cement, coniferous wood fiber, zero-dimensional conductive carbon material, one-dimensional conductive carbon material, sand, and water. The amount of coniferous wood fiber added accounts for 4 wt.%-11 wt.% of the amount of cement added, the amount of zero-dimensional conductive carbon material added accounts for 2 wt.%-13 wt.% of the amount of cement added, and the amount of one-dimensional conductive carbon material added accounts for 0.5 wt.%-4 wt.% of the amount of cement added. The mass ratio of water to cement is 2.5-3.3:
1. By weight percentage, cement accounts for 18%-30% of the raw materials of the electrode material.
15. The capacitor according to claim 14, characterized in that, In the process of preparing the first electrode intermediate, a layer of electrode slurry is laid flat in the mold, a current collector is laid flat on the electrode slurry, and then another layer of electrode slurry is laid flat on the current collector and dehydrated to form the first electrode intermediate. And / or, In the process of preparing the capacitor intermediate, an electrolyte-wetted membrane layer is laid flat on a first electrode intermediate. Then, an electrode slurry, a current collector, and another layer of electrode slurry are sequentially laid flat on the membrane layer, followed by dehydration treatment to obtain the capacitor intermediate composed of a first electrode intermediate, an electrolyte-wetted membrane layer, and a second electrode intermediate stacked in sequence; and / or, The aforementioned membrane layer containing the electrolyte is obtained by immersing the membrane material in the electrolyte until saturation; and / or, The pressure holding time after the pressurization treatment is 5-60 minutes; and / or, The pressure of the pressurization process is 15-25 MPa; and / or, The conditions for the curing treatment are: temperature 20-30℃, relative humidity 90%-100%; and / or, The thickness of the electrode paste layer spread on either side of the current collector is 1~3cm; and / or, The thickness of the current collector is 1~3mm; and / or, The membrane layer is a glass fiber mesh and / or a porous polymer membrane; and / or, The electrolyte comprises potassium hydroxide and / or lithium hydroxide; and / or, The thickness of the diaphragm layer is 1~8mm; and / or, The dehydration process involves removing moisture to below 20%, further controlling it to 0.01%-20%, even further controlling it to 0.5%-20%, or 1%-20%, or 5%-20%, or 10%-19%, or 12%-18%.
Citation Information
Patent Citations
Preparation method of cement-based supercapacitor
CN118430985A
Full-cement-based supercapacitor and preparation method thereof
CN119852100A
